2017
DOI: 10.1177/2049463717736787
|View full text |Cite
|
Sign up to set email alerts
|

The use of fentanyl in pain management in head and neck cancer patients: a narrative review

Abstract: Fentanyl transdermal therapeutic system (TTS) seems to be an important option, thanks to the way of administration, the good safety and tolerability profiles to control baseline pain. For breakthrough cancer pain (BTcP), several formulations of transmucosal fentanyl are available. All the formulations seem to be active and safety but we lack head-to-head studies of fentanyl versus other strong opioids, as well as with different formulation of fentanyl, particularly for BTcP where H&N cancer population is very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Moreover, we also previously demonstrate that level of satisfaction was significantly associated with the use of fastest onset opioids, especially fentanyl pectin nasal spray (FPNS). 2 , 6 , 7 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we also previously demonstrate that level of satisfaction was significantly associated with the use of fastest onset opioids, especially fentanyl pectin nasal spray (FPNS). 2 , 6 , 7 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Transdermal fentanyl can be useful in opioid-naïve patients with nausea, vomiting, and problems with swallowing and is usually a good option in head and neck cancers, due to safety and tolerability profiles to control baseline pain [ 65 ]. Fentanyl and buprenorphine are indeed the safest opioids in patients with chronic kidney disease stage 4 or 5 (estimated glomerular filtration rate < 30 mL/min) [ 31 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that transdermal patches are preferred in patients with head and neck cancer to control baseline pain, since oral medication could be difficult to administer [ 79 ]. An early study examining the time trends and characteristics of prescribing opioids for patients with a variety of cancers, showed that fentanyl was prescribed 10.2% of the time during the last 3 months, particularly in head and neck cancer cases using transdermal patches on most occasions.…”
Section: Transdermal Drug Deliverymentioning
confidence: 99%
“…The efficacy, safety, and quality of life of head and neck cancer patients using fentanyl transdermal patches were also evaluated in a variety of prospective studies to show a significant decrease in pain, a better quality of life, and reduced side effects, the most common being nausea and vomiting [ 80 , 81 , 82 ]. However, there is a lack of studies that compare Fentanyl transdermal patches with other opioid analgesics [ 79 ]. One notable randomized controlled trial by Haumann et al was performed on 52 head and neck cancer patients experiencing severe neuropathic pain [ 83 ].…”
Section: Transdermal Drug Deliverymentioning
confidence: 99%